Evaluation and Management of Patients with Leg Swelling: Therapeutic Options for Venous Disease and Lymphedema - Scherer, Kimberly; Khilnani, Neil (Seminars in Interventional Radiology, 2021)
Lower extremity swelling is a common condition which has a variety of etiologies and can be challenging to diagnose and manage. Swelling is usually the result of the accumulation of interstitial fluid in the subcutaneous tissues. Common etiologies include systemic, superficial, and deep venous, and lymphatic disorders. Leg swelling can occur bilaterally or unilaterally, with venous disorders being one of the most common causes of unilateral lower extremity edema.
Keywords: edema; lymphedema; venous insufficiency; interventional radiology